Shoulder Structure and Function Following the Modified Latarjet Procedure: A Clinical and Radiological Review. Issue 1 (January 2014) - Garewal, Devinder; Evans, Mathew; Taylor, David; Hoy, Gregory A.; Barwood, Shane; Connell, David
Background: To evaluate the clinical and radiological outcomes of the modified Latarjet procedure for traumatic, antero-inferior glenohumeral joint instability. Methods: Case series were used with a mean follow-up of 21.3 months for clinical and radiological review and 47.2 months for recurrent instability. Shoulder function was evaluated by clinical examination and validated shoulder scales: Western Ontario Shoulder Stability Index (WOSI), Melbourne Instability Shoulder Score (MISS) and l'Insalata Shoulder Questionnaire. Shoulder structure was evaluated by computed tomography. Results: Thirty-two cases were enrolled (mean age 27.0 years). One patient reported a redislocation during the follow-up period. Clinical examination revealed that the median external rotation (at 0° and 90° abduction) was reduced on the operative side by 7.5° ( p < 0.01) and 10° ( p < 0.001), respectively. Subjective shoulder function was good. Mean (SD) scores on the WOSI, MISS and l'Insalata scales were 78.0 (19.7), 75.8 (11.5) and 89.3 (9.9), respectively. No loss of subscapularis strength was identified ( p > 0.05). Radiological evaluation revealed a mean (SD) pre-operative glenoid surface area loss of 169.5 (48.5) mm 2 reconstituted surgically by a bone block of 225.4 (73.8) mm 2 . Subscapularis muscle bulk was reduced on the operative side, above the level of the muscle split ( p < 0.05). Conclusions: The Latarjet procedure reliably restores lost glenoid surface area, shoulder stability, strength and function. A small loss of external rotation is expected and related to altered subscapularis anatomy.